2019
DOI: 10.1111/1755-0998.13105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fish communities using environmental DNA: Effect of spatial sampling design in lentic systems of different sizes

Abstract: Freshwater fish biodiversity is quickly decreasing and requires effective monitoring and conservation. Environmental DNA (eDNA)‐based methods have been shown to be highly sensitive and cost‐efficient for aquatic biodiversity surveys, but few studies have systematically investigated how spatial sampling design affects eDNA‐detected fish communities across lentic systems of different sizes. We compared the spatial patterns of fish diversity determined using eDNA in three lakes of small (SL; 3 ha), medium (ML; 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 51 publications
1
69
0
Order By: Relevance
“…For example, a single sampling event in each season represents a snapshot of diversity, whereas longitudinal eDNA studies often sample multiple times in a season (Berry et al., 2019; Milhau et al., 2019; Zhang et al., 2019), improving the detections of seasonal variation in species composition and biodiversity. Additionally, the pooling of biological replicates reduces the signal and detection of rare species (Sato et al., 2017; Zhang et al., 2020), which are often of conservation concern (Franklin et al., 2019) and a single PCR replicate captures less taxonomic diversity than duplicates or triplicates (Beentjes et al., 2019). The small sample size of springs ( n = 4) and representation of spring types (large, naturally flowing, and unmodified springs vs. small or modified springs) directly affects vegetation comparisons, as water availability may be limiting the support of a riparian plant community (Sada et al., 2005) and indirectly animal communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a single sampling event in each season represents a snapshot of diversity, whereas longitudinal eDNA studies often sample multiple times in a season (Berry et al., 2019; Milhau et al., 2019; Zhang et al., 2019), improving the detections of seasonal variation in species composition and biodiversity. Additionally, the pooling of biological replicates reduces the signal and detection of rare species (Sato et al., 2017; Zhang et al., 2020), which are often of conservation concern (Franklin et al., 2019) and a single PCR replicate captures less taxonomic diversity than duplicates or triplicates (Beentjes et al., 2019). The small sample size of springs ( n = 4) and representation of spring types (large, naturally flowing, and unmodified springs vs. small or modified springs) directly affects vegetation comparisons, as water availability may be limiting the support of a riparian plant community (Sada et al., 2005) and indirectly animal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Water and sediment samples for each site were treated separately for the library preparation and although pooling replicates for each sample type reduces the detection of rare taxa, it does not substantially affect comparisons of communities (Sato et al., 2017; Zhang et al., 2020). Critically, pooled replicate samples can provide information about the presence of species that were observed by traditional methods, a major goal of our study.…”
Section: Methodsmentioning
confidence: 99%
“…When the number of samples is increased, to improve work efficiency and reduce analysis cost, researchers may consider pooling the water samples from multiple locations for subsequent processing. However, Sato et al [46] and Zhang et al [47] demonstrated that pooled samples decreased species detection compared to using individually processed samples, indicating that sample pooling is not useful for assessing fish assemblages. Thus, we do not recommend pooling samples for subsequent analysis.…”
Section: Sample Volume Depths and Amount Of Watermentioning
confidence: 99%
“…Thus, we do not recommend pooling samples for subsequent analysis. In addition, for lentic systems such as lakes, shoreline sampling with surface water can capture most fish species eDNA [47]. We recommend that shoreline sampling can be used to briefly survey lentic systems, whereas systematic spatial sampling should be used in subtle spatial distribution pattern surveys for entire fish species in large lentic systems (e.g., a lake with a surface area of 4343 ha [47]).…”
Section: Sample Volume Depths and Amount Of Watermentioning
confidence: 99%
See 1 more Smart Citation